Certain Analytic Formulas Linked to Locally Fractional Differential and Integral Operators. (14th July 2022) - Aldawish, Ibtisam; Ibrahim, Rabha W.
Abstract : The present investigation is aimed at defining different classes of analytic functions and conformable differential operators in view of the concept of locally fractional differential and integral operators. We present a novel generalized class of analytic functions, which we call it locally fractional analytic functions in the open unit disk. For the suggested class, we look at conditions to get the starlikeness and convexity properties.